Boosting the Brain Delivery of Atazanavir through Nanostructured Lipid Carrier-Based Approach for Mitigating NeuroAIDS - Saif Ahmad Khan (Pharmaceutics, 2020)
Atazanavir (ATZ) presents poor brain availability when administered orally, which poses a major hurdle in its use as an effective therapy for the management of NeuroAIDS. The utilization of nanostructured lipid carriers (NLCs) in conjunction with the premeditated use of excipients can be a potential approach for overcoming the limited ATZ brain delivery. Methods: ATZ-loaded NLC was formulated using the quality by design-enabled approach and further optimized by employing the Box–Behnken design. The optimized nanoformulation was then characterized for several in vitro and in vivo assessments. Results: The optimized NLC showed small particle size of 227.6 ± 5.4 nm, high entrapment efficiency (71.09% ± 5.84%) and high drug loading capacity (8.12% ± 2.7%). The release pattern was observed to be biphasic exhibiting fast release (60%) during the initial 2 h, then trailed by the sustained release. ATZ-NLC demonstrated a 2.36-fold increase in the cumulative drug permeated across the rat intestine as compared to suspension. Pharmacokinetic studies revealed 2.75-folds greater Cmax in the brain and 4-fold improvement in brain bioavailability signifying the superiority of NLC formulation over drug suspension. Conclusion: Thus, NLC could be a promising avenue for encapsulating hydrophobic drugs and delivering it to their target site. The results suggested that increase in bioavailability and brain-targeted delivery by NLC, in all plausibility, help in improving the therapeutic prospects of atazanavir.